2015
DOI: 10.1124/dmd.114.061200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Characterization of 13 CYP2C9 Allelic Variants Found in Chinese Han Population

Abstract: Our previous study detected totally 35 CYP2C9 allelic variants in 2127 Chinese subjects, of whom 21 novel alleles were reported for the first time in Chinese populations. The aim of the present study was to characterize the 13 CYP2C9 allelic variants both in vitro and in vivo. Different types of CYP2C9 variants were highly expressed in COS-7 cells, and 50 mM tolbutamide was added as the probing substrate to evaluate their metabolic abilities in vitro. Subsequently, the concentrations of tolbutamide and its met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Those variants either lacked functional characterization or had not been previously reported. The standard strategy to identify the functional significance of variants begins with the preparation of recombinant allozymes using site-directed mutagenesis followed by expression in human cell lines, measurement of protein concentrations, and determination of enzyme activity using prototypic substrates (Weinshilboum et al, 1999;Wang et al, 2003Wang et al, , 2005DeLozier et al, 2005;Dai et al, 2014aDai et al, ,b, 2015Niinuma et al, 2014;Hu et al, 2015). Computational methods have also been developed in an attempt to predict the effect of genetic variation in encoded amino acid sequence on protein stability and enzyme activity, but their validation and accuracy remains unclear (Flanagan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Those variants either lacked functional characterization or had not been previously reported. The standard strategy to identify the functional significance of variants begins with the preparation of recombinant allozymes using site-directed mutagenesis followed by expression in human cell lines, measurement of protein concentrations, and determination of enzyme activity using prototypic substrates (Weinshilboum et al, 1999;Wang et al, 2003Wang et al, , 2005DeLozier et al, 2005;Dai et al, 2014aDai et al, ,b, 2015Niinuma et al, 2014;Hu et al, 2015). Computational methods have also been developed in an attempt to predict the effect of genetic variation in encoded amino acid sequence on protein stability and enzyme activity, but their validation and accuracy remains unclear (Flanagan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The mean warfarin dose in carriers of CYP2C9*non-3 significantly decreased. Many in vivo and in vitro studies have demonstrated that rare variants are often associated with decreased drug metabolic activity, and only a few rare variants show increased or unchanged metabolic activity ( 12 , 14 , 31 ). Two studies assessed the in vitro catalytic activities of over 30 rare alleles in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…The total CYP2C9*non-3 allele frequency is 2.58%. In vitro and in vivo studies have demonstrated that most of these are associated with lower drug metabolic activities ( 12 14 ). This indicates that CYP2C9*non-3 variants are not uncommon in the Chinese Han population, and similar to *3, carriers with these variants may have lower warfarin dose requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, no substantial differences in CL/F were found among racial/ethnic groups. The frequency of CYP2C9 mutant alleles is higher in whites ( *2 , 12%; *3 , 8.3%) than in Chinese people ( *2 , 0%; *3 , 3.3%) . However, only CYP2C9*3 shows a significant effect on the pharmacokinetics of several CYP2C9 substrates, such as angiotensin‐receptor blockers (losartan, candesartan, and irbesartan), oral hypoglycemic agents (glyburide and tolbutamide), and nonsteroidal anti‐inflammatory drugs (ibuprofen and celecoxib) .…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P‐450 (CYP)2C9 is the major enzyme responsible for AZL metabolism. Because the frequency of CYP2C9 polymorphic alleles shows marked interethnic variation, AZL pharmacokinetics may also differ among people of different ethnicities; indeed, such variation has been observed in the case of other CYP2C9 substrates such as pioglitazone . However, thus far, the pharmacokinetics of AZL in the Chinese population has not been investigated.…”
mentioning
confidence: 99%